Unveiling the Influence of Gender Roles in Children's Sexual Education - Suud Sarim Karimullah (LPPM IAIN Parepare, 2023)
This study highlights the importance of a deep understanding of gender as a key foundation in understanding identity, sexual rights, and the dynamics of healthy interpersonal relationships. Through library research, this study summarizes, evaluates, and integrates previous findings to gain a comprehensive understanding. The results of the study confirmed that sexual education approaches that consider gender roles are able to overcome stereotypes and promote gender equality. Effective sexual education not only expands knowledge but also has a substantial impact on the health and well-being of children. It includes a deeper understanding of sexual health, the ability to make wise decisions in interpersonal relationships, and support for mental health. In addition, the important role of teachers and parents in providing sexual education cannot be underestimated. Teachers help deliver inclusive and accurate sexual education, while parents have a significant role to play in facilitating open communication in the home environment. The involvement of both has a central role in forming a solid foundation for better understanding and a more holistic approach to continuing sexual education.